The effect of aeration rate and feedstock density on biodrying performance for wet refuse-derived fuel quality improvement - Tanik Itsarathorn; Sirintornthep Towprayoon; Chart Chiemchaisri; Suthum Patumsawad; Awassada Phongphiphat; Abhisit Bhatsada; Komsilp Wangyao (International Journal of Renewable Energy Development, 2023)
This study investigates the effect of aeration rate and feedstock density on the biodrying process to improve the quality of type 2 wet refuse-derived fuel. The aeration rate and feedstock density were varied to investigate these parameters’ effect on the system’s performance. The experiments used 0.3 m3 lysimeters with continuous negative ventilation and five days of operation. In Experiment A, aeration rates of 0.4, 0.5, and 0.6 m3/kg/day were tested with a feedstock bulk density of 232 kg/m3. In Experiment B, the optimum aeration rates determined in Experiment A (0.5 and 0.6 m3/kg/day) were used, and the feedstock density was varied (232 kg/m3, 250 kg/m3, and 270 kg/m3). The results showed that an aeration rate of 0.5 m3/kg/day was the most efficient for a feedstock density of 232 kg/m3; when the aeration rate was increased to 0.6 m3/kg/day, a feedstock density of 250 kg/m3 was the most effective. However, a feedstock density of 270 kg/m3 was not found to be practical for use in the quality improvement system. When the feedstock density is increased, the water in the feedstock and the water resulting from the biodegradation process cannot evaporate due to the feedstock layer’s low porosity, and the system requires an increased aeration rate. Furthermore, the increase in density scaled with increased initial volatile solid content, initial organic content, and initial moisture content, which significantly impacted the final moisture content based on multivariate regression analysis.